Rules for Germination Test of Tree Seeds for Certification - Gupta, R. N.; Pattanath, P. G.; Kumar, Adarsii; Thapliyal, R. C.; Raturi, A. S. (Indian Forester, 1975)
In order that results may be reproduceable, it is essential that germination tests for certification of seeds are standardised. The International Seed Testing Association has laid down guide lines for these tests in 1966, and based on these lines it is necessary to standardize the procedures for each species separately. In this connection, rules for germination tests of 55 Indian tree species have been worked out and tabulated.